Glycolipids implicated as mediators of clinically visible retinal pigment epithelial migration in age-related macular degeneration - Zhen Wang; David M. G. Anderson; Jeffrey D. Messinger; Christine A. Curcio; Kevin L. Schey (Proceedings of the National Academy of Sciences, 2025)
The retinal pigment epithelium (RPE) is the metabolic gatekeeper to the photoreceptors, thus playing many essential roles in healthy vision. Under certain conditions, RPE cells may transdifferentiate and migrate from the RPE layer. Ectopic RPE cells are potential signal sources for hyperreflective foci, prominent clinically visible biomarkers in age-related macular degeneration, which causes central vision loss globally. Applying multiple imaging modalities including ex vivo optical coherence tomography, autofluorescence microscopy, and imaging mass spectrometry (IMS) to human retina tissue, we compared lipid profiles in ectopic and orthotopic RPE cells. Our results showed that ectopic RPE cells share some molecular signatures with normal RPE cells as revealed through autofluorescence imaging and IMS. In both orthotopic and ectopic RPE cells, IMS detected phosphatidylglycerol, PG 36:2, and several triacylglycerols containing long-chain fatty acids. GM3 gangliosides (40:1, 42:1, and 42:2) were also detected in ectopic RPE cells with differences in abundance in different populations of ectopic RPE cells. Lactosylceramide (LacCer 44:5) and glucosylceramide (GlcCer 44:5) were found exclusively in ectopic RPE cells. In contrast, ectopic RPE did not exhibit signals of phosphatidylinositols (PI) (PI32:0, PI32:1, PI34:1, and PI34:2) normally detected in RPE cells. Near-single-cell resolution IMS results suggest that RPE transdifferentiation, with loss of normal functions and gain of new functions like migration, may be linked to altered metabolism of glycosphingolipids and PIs.